A new algorithm for determining deciphering delay of regular language. - Thắng, Đặng Quyết; Hân, Nguyễn Đình; Huy, Phan Trung (Journal of Computer Science and Cybernetics, 2012)
In this paper, we propose a new algorithm determining deciphering delay of regular language, which recognizes by a finite automaton  A. The algorithm has time complexity O(n^3), where n is the number of states and edges of  A.